Punctuation power : punctuation and how to use it - Terban, Marvin (New York : Scholatic Inc., 2000)
Explains the purpose and importance of punctuation and how it is used, covering apostrophes, colons, commas, exclamation points, hypens, parentheses, slashes, and more.
Keywords: English language -- Punctuation -- Handbooks, manuals, etc. -- Juvenile literature; English language -- Punctuation